Survival of Escherichia coli O157:H7 and Listeria monocytogenes in an acidified low-fat mayonnaise based hibachi sauce. (July 2019) - Hwang, Daizy; White, Elizabeth; Purohit, Anuj; Mohan, Anand; Mishra, Abhinav
Abstract: Survival of pathogenic bacteria under acidic conditions may pose a significant food safety challenge and should be assessed when developing new food products. The objective of this study was to determine the antimicrobial effect of two acidulants against Escherichia coli O157:H7 and Listeria monocytogenes in a low-fat mayonnaise based hibachi sauce subjected to different preparation and storage conditions. A mixture of seasoning and acidulants was heated to 82.2 °C and cooled. This was combined with a low-fat mayonnaise and acidified with either 0.25 g lactic acid/100 g sauce, 0.25 g, or 0.5 g vinegar/100 g sauce. The sauce was then inoculated with L. monocytogenes and E. coli O157:H7 at the levels of ca. 6 log CFU/g each, and stored at 4 or 23 °C. Both pathogens survived longer at 4 than at 23 °C (P < 0.001). Acidulant significantly affected survival of both bacteria (P < 0.001) with the order of average antimicrobial efficacy being 0.25 and 0.5 g lactic acid/100 g sauce > 0.5 g vinegar/100 g sauce > unacidified control. At 23 °C, populations of both bacteria decreased by at least 4 log CFU/g after 72 h of storage in formulations containing 0.25 g lactic acid/100 g sauce. Acidification with lactic acid can improve food safety of mayonnaise based sauces in case of post processing contamination. Highlights: Survival of L. monocytogenes and E. coli O157:H7 in a hibachi sauce was evaluated. Acidified low-fat mayonnaise based hibachi sauce was stored at either 4 or 23 °C. 0.25 g/100 g lactic acid had higher antimicrobial activity than 0.5 g/100 g vinegar. 0.25 g/100 g lactic acid provided >4 log CFU/g reduction of the two pathogens. Storage at 23 °C resulted in quicker reduction of pathogen populations than at 4 °C.